Implementation and Access to Pre-exposure Prophylaxis for Human Immunodeficiency Virus by Men Who Have Sex With Men in Europe - Sepodes, Bruno; Rocha, João; Batista, Jorge; Figueira, Maria-Eduardo; Dráfi, František; Torre, Carla (Frontiers in Medicine, 2021)
Preexposure Prophylaxis (PrEP) is a significant public health intervention with proven efficacy and safety in the prevention of Human Immunodeficiency Virus (HIV) infection, that has taken a considerable amount of time to reach Europe, in relation to their transatlantic counterparts, namely the United States of America (USA). There, it perceived as being an essential prevention tool to be integrated within existing medical, behavioral and structural interventions in place for the management and containment of HIV infection in men who have sex with men (MSM). In a region such as Europe, with approximately double the USA population, it is estimated that not even 10% have proper access to PrEP and given the lack of coordination with healthcare, at their own expense. Here, we identify the reasons behind the 4 years lag in the approval of PrEP in the European Union/European Economic Area (and Europe in general) and explore the efficacy and effectiveness of PrEP needed to be confirmed with some implementation or demonstration studies conducted in the region. Independently of the data gathered, access of MSM to PrEP is far from ideal in Europe and much still needs to be done. The demonstration of the cost-effectiveness of PrEP alongside with other social and behavioral factors need to be addressed, while the clear populations within MSM that will benefit from this intervention are properly identified and make use of the latest recommendations of the World Health Organization that consider not only daily PrEP but also event-driven PrEP. The momentum for the proper implementation of PrEP in the EU is not lost, and with the existence of generics and even new formulations, there is a renewed opportunity for unleashing the public health benefits arising from this pharmacological tool with other interventions in place (e.g. condoms, testing and counseling).